Static Light Scattering for Lignin Particle Size Characterization - Makkonen, Janita; Ahvenainen, Patrik; Bertella, Stefania; Kellock, Miriam; Saha, Sanjib; Huber, Klaus; Farooq, Muhammad; Österberg, Monika; Penttilä, Paavo (Particle & Particle Systems Characterization)
Abstract Lignin, a widely available and renewable organic polymer, has several desirable properties and applications. However, as a by‐product of pulp and paper industry, it is mainly burned for energy. Limited understanding of the complex and heterogeneous structure and a shortage of tailored analysis methods hinder its utilization in higher value applications. This study describes and compares the use of two different static light scattering methods, laser diffraction and small‐angle light scattering (SALS), for studying lignin particle size in suspension. The results from laser diffraction showed that the selected particle concentration and absorption coefficient affect the measured sizes especially for particles <1 µm in diameter. For irregularly shaped particles with broad size distributions, sampling is the most important parameter affecting the results. SALS proved an efficient method for obtaining information on particle aggregation by providing primary particle sizes as well as aggregate sizes. Characterization of samples with spherical particles and narrow size distributions is straightforward with both laser diffraction and SALS, whereas the interpretation of results for more heterogeneous samples is less obvious. Static light scattering methods could make lignin particle size analysis more rapid and automated, thus enhancing lignin valorization, but should be applied carefully to avoid systematic errors.

In-Situ Determination of the Charging of Nanometer and Submicron Particles at High Temperatures - Schiel, Annette; Weber, Alfred P.; Kasper, Gerhard; Schmid, Hans-Joachim (Particle & Particle Systems Characterization)
Thermal charging of submicron and nanometer particles has been studied for model aerosols of TiO2 and SiO2 as well as Al-Si (aluminosilicate) at 1 000 °C with a new quasi in-situ technique. The size dependence of the particle separation efficiency for electrostatic precipitation was determined. The charging state of the particles was obtained from evaluating the global Deutsch number for precipitation in an electric field applied to a laminar flow based on particle trajectory considerations.

In-Situ Measurement of Local Particle Flux Densities in a Complex Two-Phase Flow - Schmid, Hans-Joachim; Veith, Susanne; Umhauer, Heinz (Particle & Particle Systems Characterization)
An optical measuring technique is presented allowing the exact in-situ measurement of local particle flux densities in a confined channel flow by counting single particles penetrating an optically well defined measuring volume. This enables a precise flux determination up to the direct vicinity of planar walls. The measurement set-up and its calibration as well as the whole test facility are described in detail. This measurement technique is used to study the particle transport in electrostatic precipitators. Exemplarily, results of particle flux profiles as well as precipitation, as gained from balances of parts of the precipitator channel, are presented. Furthermore, the possibility to determine particle velocity fluctuations is demonstrated.